ETHICS OF SPORTS AND SPORTSMANSHIP IN CONTEMPORARY TIMES (International Journal of Food and Nutritional Sciences, 2022)
Today sports events are close to battles: winning at any cost is what matters. As a result sports has been increasingly witnessing a complete disregard for sports ethics Now-a-days the influence of the money factor in sports is so great that not only contestants ready to go to any length to win a match but also they are ready to cheat, lie. Thus cheating, lying, bribery, violence and doping have become almost essential in sports and these unethical practices kills sportsmanship spirit. People need to contemplate how to retain dignity and grace in defeat. Use of wrong means to achieve a victory is degrading to very spirit of sports and humanity. Players and Spectators need to realize that one side has to win and the others has to lose after all in any game. SPORTS events are essentially social in character. They facilitate the coming together of people from various parts of the country, at a national level, and various parts of the world, at the international level. Sports make people cross cultural barriers and speak a language that is understood by all.The World Sports Congress, held in New Delhi, emphasized that sports could play a major role in promoting and propagating peace, provided one understood the spirit of global participation and the philosophy of sports. This philosophy of sports is based on the assumption that a "game will be played in the spirit of the game". Rules of decency and decorum will on no account be violated by all those related to sports. The spirit of sports is to embody a combination of qualities such as fairness, courtesy, generosity, grace and decency or in one word sportsman ship. Sports does not simply involve players, spectators, sports authorities, media, sponsors, in fact each and every group faction that is even only associated with sports a fundamental part of an event. And all of them, then, are expected to maintain a code of conduct and nurture the sporting spirit